Can crop diversification of perennial crop by smallholder farmers explained by risk attitudes and time preferences? - Arieska Wening Sarwosri; Oliver Mußhoff (GOEDOC, Dokumenten- und Publikationsserver der Georg-August-Universität, 2019)
This study examines whether the decision of crop diversification for perennial crops is based on underlying risk attitudes and time preferences. We conducted incentivised field experiments on Sumatra Island, Indonesia, involving farmers who cultivate rubber and farmers who cultivated rubber and oil palm trees, i.e., undertook crop diversification. We estimated risk attitudes and time preferences jointly. The results indicated that farmers who undertook crop diversification were statistically significantly more risk-averse than rubber farmers. However, the time preferences between the two groups were not statistically significantly different.
urn:nbn:de:gbv:7-webdoc-3993-4
Keywords: 330; crop diversification; oil palms; risk attitudes; rubber; time preference